2009
DOI: 10.1128/jb.00262-09
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Sensitivity of Blue-Light-Dependent Signaling Mediated by AppA/PpsR or PrrB/PrrA in Rhodobacter sphaeroides

Abstract: Formation of photosynthesis complexes in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…As long as oxygen is available, Rhodobacter performs aerobic respiration. However, at intermediate oxygen tension blue light, even at low intensities, prevents AppA from binding to PpsR and photosynthesis genes are repressed (8,9), reducing the accumulation of the harmful singlet oxygen. The PrrB/PrrA two-component system senses the electron transport through the cbb3 oxidase and induces transcription of photosynthesis genes at very low oxygen tension or in the absence of oxygen (5,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…As long as oxygen is available, Rhodobacter performs aerobic respiration. However, at intermediate oxygen tension blue light, even at low intensities, prevents AppA from binding to PpsR and photosynthesis genes are repressed (8,9), reducing the accumulation of the harmful singlet oxygen. The PrrB/PrrA two-component system senses the electron transport through the cbb3 oxidase and induces transcription of photosynthesis genes at very low oxygen tension or in the absence of oxygen (5,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…More broadly speaking, it is also a new member of the family of blue light-photoactive proteins; bluegreen light is a ubiquitous environmental signal that activates a functionally diverse range of bacterial proteins, such as photoactive yellow protein (PYP) (26,27) and those containing LOV (28 -31) or BLUF domains (32)(33)(34)(35). Recent data available from genome sequencing as well as structural and functional characterization of these sensory proteins and their relatives have revealed that they share some general features in the structural basis of photoresponsiveness and signal transduction (36,37).…”
mentioning
confidence: 99%
“…Current experimental data suggest that metabolismdependent chemotaxis may be more complex than previously thought, owing to differential gene expression in different environments. For example, PrrB/PrrA two-component system up-regulates photosynthesis in R. sphaeroides, and the expression is stimulated by low oxygen conditions [55]. This implies that at very low concentration, oxygen may no longer be an attractant, but may cause bacteria to start phototaxis.…”
Section: Discussionmentioning
confidence: 99%